KONTRIBUSI GURU PAI DALAM PEMBINAAN ETIKA BERPAKAIAN ISLAMI SISWA SMAN KOTA SABANG - Mujiburrahman Mujiburrahman (Islam Futura, 2015)
Coaching Islamic dress is one of the tasks that must be implemented by Islamic education knowledge (Pendidikan Agama Islam/PAI) teachers, both in school and out of school. Contribution PAI teachers are expected to have relevance to the role of educators in Islam, so that the teacher's role in fostering ethical PAI Islamic dress can give a good change to students. This research was conducted at SMAN Sabang, which is considered representative for the study, because students and teachers are very homogeneous, tribes, nations and religions. This research is a qualitative research with method of collecting data through interviews, observation and document study. The researcher found that 1) Ethics dress that is set the school has met the criteria of Islamic dress code; but students' practicing islamic dress both in school and out of school is less than perfect. 2) the contribution of PAI teachers in coaching dress code is good. 3) In coaching, PAI teachers have enabling and inhibiting factors, so that there are students who still dress out of school environment do not meet the criteria of Islamic dress.